(untitled) (Revista Iberoamericana de Bioética, 2024)
Understanding the opinions of doctors on compulsory hospitalization as a strategy for rescuing mental health and the autonomy of substance-dependent patients. A descriptive and exploratory study from a qualitative approach, conducted at a specialized psychiatric hospital. The research subjects consisted of seven physicians. The study used an instrument for participant characterization, together with a semi-structured interview script. Two final categories originated from the convergence of initial categories obtained from content analysis. In the first category, labelled “Compulsory Hospitalization: Autonomy, Patients’ Rights, and Professionals’ Rights and Responsibilities,” two subcategories emerged: Compulsory hospitalization is necessary due to social risk, and the ethical and technical aspects of this practice; and Compulsory Hospitalization: loss of freedom or a new beginning? The second category was labelled “Multidisciplinary Team: Process of Social Integration.” The results indicated that compulsory hospitalization is beneficial as long as it serves a therapeutic purpose, prioritizing the preservation of the patient’s integrity./p>